International clinical guidelines for the management of phosphomannomutase 2-congenital disorders of glycosylation: Diagnosis, treatment and follow up - Altassan, Ruqaiah; Hutter, Anna-Marlen; Thiel, Christian (Journal of inherited metabolic disease, 2019)
Phosphomannomutase 2 (PMM2-CDG) is the most common congenital disorder of N-glycosylation and is caused by a deficient PMM2 activity. The clinical presentation and the onset of PMM2-CDG vary among affected individuals ranging from a severe antenatal presentation with multisystem involvement to mild adulthood presentation limited to minor neurological involvement. Management of affected patients requires a multidisciplinary approach. In this article, a systematic review of the literature on PMM2-CDG was conducted by a group of international experts in different aspects of CDG. Our managment guidelines were initiated based on the available evidence-based data and experts' opinions. This guideline mainly addresses the clinical evaluation of each system/organ involved in PMM2-CDG, and the recommended management approach. It is the first systematic review of current practices in PMM2-CDG and the first guidelines aiming at establishing a practical approach to the recognition, diagnosis and management of PMM2-CDG patients.
Gesehen am 29.10.2019